Trategi Pencegahan Cyberbullying: Studi Persepsi Mahasiswa tentang Normalisasi Cyberbullying di Media Sosial - Suhadah, Suhadah; Khotimah, Husnul; Adawiyah, Rabiatul; Suswandi, Suswandi; Dwi Wulandari, Enza; Andika, Angga; Fahdil, Fahdil (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to explore the perceptions of students of Universitas Muhammadiyah Mataram towards the normalization of cyberbullying on social media and to formulate appropriate prevention strategies. This study uses a qualitative approach with a descriptive exploratory design. The results of the study indicate that the normalization of cyberbullying occurs due to the lack of social regulation in digital media, low digital literacy, and negative influences from the family and school environment. Students identified forms of cyberbullying such as body shaming, public insults, and hurtful jokes as part of interactions that are often considered "normal". Suggested prevention strategies include digital education, social campaigns, parental and school involvement, and the application of legal sanctions. The conclusion of this study emphasizes the importance of the active role of students as agents of change in creating a healthy and safe digital space through good interaction ethics, as well as building collective awareness of the dangers of normalizing negative behavior on social media. Keywords: Cyberbullying, Normalization, Prevention Strategies, Social Media, Students.